Kinetics and Substrate Partitioning in the Polyphenol Oxidase-Catalysed Oxidation of Catechol in a Two-Phase System - Tyas Utami; D.L Pyle (Indonesian Association of Food Technologists, 1998)
The kinetics of catechol oxidation catalysed by polyphenol oxidase in two-phase systems with mixtures of lauryl alcohol and hexane as the solvent phase is investigated, with particular reference to the effect of partitioning of catechol on the enzyme kinetics. Theory is developed to derive a relationship between the apparent K. and the intrinsic or 'true' Kn. The theory predicts that substrate partitioning should not change %Cue but that the relationship between the apparent and intrinsic K,, values should depend on the phase volume ratio and the partition coefficient. The theory shows good agreement with the results and gives a consistent K. value.